2017
DOI: 10.1080/03639045.2017.1408643
|View full text |Cite
|
Sign up to set email alerts
|

Oral bioavailability enhancement of raloxifene by developing microemulsion using D-optimal mixture design: optimization and in-vivo pharmacokinetic study

Abstract: The objective of this work was to utilize a potential of microemulsion for the improvement in oral bioavailability of raloxifene hydrochloride, a BCS class-II drug with 2% bioavailability. Drug-loaded microemulsion was prepared by water titration method using Capmul MCM C8, Tween 20, and Polyethylene glycol 400 as oil, surfactant, and co-surfactant respectively. The pseudo-ternary phase diagram was constructed between oil and surfactants mixture to obtain appropriate components and their concentration ranges t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The transmittance value (96.95%) is close to predicted values (97.57%). This result confirms the validation of the model and the efficient emulsification of the different components [24,46].…”
Section: Physico-chemical Characteristicssupporting
confidence: 85%
See 1 more Smart Citation
“…The transmittance value (96.95%) is close to predicted values (97.57%). This result confirms the validation of the model and the efficient emulsification of the different components [24,46].…”
Section: Physico-chemical Characteristicssupporting
confidence: 85%
“…A D-optimal mixture design [24] with 3 independent variables (percent content of oil, surfactant/co-surfactant mixture, and water) was used for carrying out the optimization study.…”
Section: Optimization Of Ibuprofen Microemulsion By D-optimal Experimmentioning
confidence: 99%
“… 49 As per the results of the stability study, the high stability observed with the formulated NEs is attributed to the plasticity of the interfacial film, which was maintained throughout the shelf life of NE and hindered phase separation. 50 The measured pH values of the formulated NEs were found to be appropriate for skin topical application. 24 In addition, the slightly acidic pH value observed with Vit C-loaded NE is preferable to enhance the stability of Vit C. 11 …”
Section: Discussionmentioning
confidence: 87%
“…Used to improve solubility of poorly soluble drugs [142]; medicated chewing gums [120]; bioactive dressings [128]; or tablets [121,139], oleogels [144,145], organogels for cardiovascular diseases [118], nanoparticles with amoxicillin trihydrate and thymol [131,134], novel excipients [129,136,146] and oils mixture with salicylic acid for ointment [143] formulation; itraconazole for oral [27,127], gel with loratadine [148], tablets of metformin [130], controlled release of ketoprofen [23] and excipients with finasteride [126] formulation; emulsion formulation of vitamins [119], of aceclofenac [122], of raloxifen [135], of aprepitant [123], of catechin [28], of darunavir [117], of lopinavir [116], of butenafine hydrochloride [132], of cathepsin K inhibitor [140], of telmisartan [138], of olmesartan medoxomil [137], of bovine serum albumin [141], of nelfinavir mesylate [124], of docetaxel [125], of nutraceutical products [147] and oxidative stability avocado oil [133].…”
Section: Application Of Mixture Design In Pharmaceutical Healthmentioning
confidence: 99%